Reinventing religious studies : key writings in the history of a discipline - Elliott, Scott S.; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Reinventing Religious Studies offers readers an opportunity to trace the important trends and developments in Religious Studies over the last forty years. Over this time the study of religion has been transformed into a critical discipline informed by a wide range of perspectives from sociology to anthropology, politics to material culture, and economics to cultural theory. Reinventing Religious Studies brings together key writings which have helped shape scholarship, teaching and learning in the field. All the essays are drawn from the CSSR Bulletin, a provocative, occasionally irreverent, and always critical journal which has long been at the centre of debates in Religious Studies. This collection will prove invaluable for students and scholars of theory and method in Religious Studies. It offers readers a unique opportunity to understand the history of key issues in the study of religion and what remains central to the study of religion today.
Introduction / Scott S. Elliott -- For such a time as this : the Council of Societies for the Study of Religion, 1969-2009 / Harold Remus -- Why a council on the study of religion? / Claude Welch -- Ironies / John F. Wilson -- Religious studies : the next vocation / Jacob Neusner -- Impressions from Wingspread : religious studies--the state of the art / Walter H. Capps -- History of religions / Ninian Smart -- The future of religious studies : moving beyond the mandate of the 1960s / Carl A. Raschke -- Naming the game : a question of the field / Charles Elliott Vernoff -- Neutrality in the study of religion / John H. Whittaker -- Assessing social-scientific theories of religion / Robert A. Segal -- Playing hardball in religious studies / Arvind Sharma -- The academic study of religion : a methodological reflection / Arvind Sharma -- Fending off the social sciences / Robert A. Segal -- Confessions of a former establishment fundamentalist / Robert N. Bellah -- Confessing away the soul with the sins, or the risks of Uncle Tomism among the humanists : a reply to Robert Bellah / James E. Dittes -- Criteria for organizing the introductory course in religion / James C. Livingston -- Teaching about religion at the state university : taking the issue seriously and strictly / Robert N. Minor and Robert D. Baird -- Teaching about religion at the state university : a reply / Julia Benton Mitchell and David B. Annis -- Teaching about religion at the religiously affiliated university : taking the issue seriously and strictly--a reply to Robert Baird and Robert Minor / Philip Boo Riley -- For the advancement of my career : a form critical study in the art of acknowledgment / Carol Christ and Judith Plaskow Goldenberg -- Women's studies in religion / Carol Christ -- The debut of the Bible as a pagan classic / John A. Miles, Jr. -- Bible and religion / Jonathan Z. Smith -- Contemporary socio-political change and the work of religious studies / Walter H. Capps -- The scholar of religion as a cultural critic : perspectives from Denmark / Tim Jensen -- What are the humanities and why do they matter? : the case of religion and public life / Gary Lease -- Response to Gary Lease's "What are the humanities, and why do they matter?" / Robert Hunt -- So, what are we professing here? : religion, the liberal arts, and civic life / Raymond B. Williams -- Response to Raymond B. Williams's "So, what are we professing here? Religion, the liberal arts, and civic life" / Heather Hartel -- Response to Raymond B. Williams's "So, what are we professing here? Religion, the liberal arts, and civic life" / Robert J. Stephens -- Response to Raymond B. Williams's "So, what are we professing here? Religion, the liberal arts, and civic life" / Forrest Clingerman -- Rejoinder / Raymond B. Williams -- Late capitalism arrives on campus : making and remaking the study of religion / Russell T. McCutcheon -- Religious studies and identity politics : mythology in the making / Darlene Juschka -- Toward an engaged religious studies / Brian E. Malley -- The study of religion under late capitalism, or commodity triumphant / Gustavo Benavides -- On the teaching of Islam in America / Richard C. Martin -- Reflections on teaching about September 11 / edited by Craig R. Prentiss. Terror and violence through Buddhist lenses / Stephen C. Berkwitz -- Teaching through tragedy / Patricia Zimmerman Beckman -- Teaching September 11 / Elizabeth McAlister -- Class on September 11 / Richard Salter -- Death and memory at Ground Zero : a historian of religion's report / Paul Christopher Johnson-- September 11, 2001 and Islam / Zayn Kassam.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Religion -- Study and teaching; Religion -- Methodology; Electronic books